(untitled) (Research, Society and Development, 2024)
Autism Spectrum Disorder (ASD) is of biological origin and has environmental influences. It is characterized as a neurodevelopmental disorder that is related to communication deficits, the presence of stereotyped patterns, repetitive behaviours, interest in specific activities and difficulty in social interactions. Aim: To show how nurses work with patients with ASD. Methodology: This study refers to a systematic literature review drawn up in accordance with the eight stages. This method is guided by the checklist recommended by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). In the first search, 13 articles were selected and, in the second, a further 7 papers were selected to make up this research. The eligibility criteria were: full text; time frame of the last 5 years; languages in Portuguese and Spanish; relevant to the topic. Results: ASD affects an average of 62/10,000 people, with boys being four times more prevalent. In Brazil, there are still no official statistics on its incidence. However, it is known that approximately 10% to 20% of children and adolescents suffer from some kind of mental disorder, 4% of whom require intensive multi-professional care. It is diagnosed through clinical observation, taking into account the reports of caregivers and family members who are in closest contact with the individual.